Politics of Regime Change Under the One-Party Dominant Rule in Japan: Lessons from the Rise and Fall of the Democratic Party of Japan - Iga, Tsukasa (WILAYAH: The International Journal of East Asian Studies, 2014)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.